Filipino philosophy a critical bibliography, 1774-1997 - Gripaldo, Rolando M. (Manila De La Salle University Press, 2000)
This CD-ROM contains a Word document format of the book.
Pt.1. Filipino philosophy and its bibliography -- Pt.2. The bibliography, 1774-1992 -- Pt.3. The update, 1993-1997.
Opens as a Word document.
MS Word.